Perlindungan Hukum Terhadap Sorabi Hijau Khas Karawang Sebagai Potensi Indikasi Geografis - Mutiara Sukma (IAIN Bengkulu, 2021)
Abstract: Indonesia has a wealth of natural resources that are very much and varied, of course, this is because Indonesia consists of thousands of islands which have their own diversity. Geographical indication is described in Article 1 point 6 of Law no. 20 of 2016 concerning Brands and Geographical Indications, namely, a characteristic that indicates the area of origin of an item and/or product which due to geographical environmental factors including natural factors, human factors or a combination of these two factors gives certain reputation, quality and characteristics to the goods and / or the products produced. The research aims to find out how to provide legal protection for products that are unique to an area. One area that has a unique product that can be a potential geographic indication is Karawang, Karawang is an area that focuses on the agricultural sector that produces rice, of course this has an effect on potential geographic indication products that use rice as raw material such as Sorabi, which mainly uses flour rice. Green sorabi can receive legal protection through geographic indication based on PP No. 51 of 2007 concerning Geographical Indications. The role of the government is very influential in making the typical Karawang green sorabi as a geographical indication by making people aware of how important it is to register local specialty products because it can help increase economic value for local communities.Keywords: Protection, Law, Geographical. Abstrak: Indonesia memiliki kekayaan sumber daya alam yang sangat banyak dan beraneka ragam, tentu hal tersebut dikarenakan Indonesia terdiri dari beribu pulau yang memiliki keaneka ragamannya masing-masing. Indikasi geografis dijelaskan dalam Pasal 1 angka 6 UU No. 20 Tahun 2016 tentang Merk dan Indikasi Geografis yaitu, suatu ciri khas yang menunjukkan daerah asal suatu barang dan/atau produk yang karena faktor lingkungan geografis termasuk faktor alam, faktor manusia atau kombinasi dari kedua faktor tersebut memberikan reputasi, kualitas, dan karakteristik tertentu pada barang dan/atau produk yang dihasilkan, Penelitian bertujuan untuk mengetahui bagaimana memberikan perlindungan hukum bagi produk yang berasal khas dari suatu daerah. Salah satu daerah yang memiliki produk khas yang dapat menjadi potensi indikasi geografis adalah Karawang, Karawang adalah daerah yang berfokus pada sektor pertanian yang menghasilkan beras, tentu hal tersebut berpengaruh pada produk potensi indikasi geografis yang menggunakan bahan baku beras seperti Sorabi yang bahan utamanya menggunakan tepung beras. Sorabi Hijau dapat menerima perlindungan hukum melalui indikasi geografis berdasarkan PP No. 51 Tahun 2007 Tentang Indikasi Geografis. Peran pemerintah sangat berpengaruh penting menjadikan sorabi hijau khas karawang sebagai indikasi geografis dengan cara menyadarkan masyarakat untuk mengetahui betapa pentingnya untuk mendaftarkan produk khas daerahnya karena dapat membantu menaikkan nilai ekonomi bagi masyarakat daerah.Kata Kunci: Perlindungan, Hukum, Geografis.